Pedestrians in Traffic Environments: Ultrafine Particle Respiratory Doses - Maurizio Manigrasso (International Journal of Environmental Research and Public Health, 2017)
Particulate matter has recently received more attention than other pollutants. PM10 and PM2.5 have been primarily monitored, whereas scientists are focusing their studies on finer granulometric sizes due both to their high number concentration and their high penetration efficiency into the respiratory system. The purpose of this study is to investigate the population exposure to UltraFine Particles (UFP, submicrons in general) in outdoor environments. The particle number doses deposited into the respiratory system have been compared between healthy individuals and persons affected by Chronic Obstructive Pulmonary Disease (COPD). Measurements were performed by means of Dust Track and Nanoscan analyzers. Forty minute walking trails through areas with different traffic densities in downtown Rome have been considered. Furthermore, particle respiratory doses have been estimated for persons waiting at a bus stop, near a traffic light, or along a high-traffic road, as currently occurs in a big city. Large differences have been observed between workdays and weekdays: on workdays, UFP number concentrations are much higher due to the strong contribution of vehicular exhausts. COPD-affected individuals receive greater doses than healthy individuals due to their higher respiratory rate.